Children's Day, Alaska Yukon Pacific Exposition, Seattle, June 5, 1909. - Nowell, Frank H., 1864-1950 (1909)
Children sitting on a large piece of lumber known as the ""Big Stick"", Forestry Building PH Coll 727.798 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number